Learning style awareness & academic performance - Barman, Arunodaya (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Introduction: Preferred approach to learning is one's own learning style. Learning style varies from individual to individual. When students learn in different ways; the approach preferred by them may be an important determinant in their academic performance. This study is intended to explore this association among the nursing students in Kolej Poly-Tech MARA. Methods: It was pretest-posttest experimental study. Learning style preferences of nursing students were identified using V ARK learning style inventory. Students were informed of their preferred learning style and how to utilize their learning style strengths to improve learning for better academic performance in a one day workshop. Academic achievements of students in terms of GP A for the three consecutive examinations, two held before and one held after the workshop were collected from the academic departments. Repeated measure ANOV A was done to compare the GP As obtained by the students in those three examinations. Results: Study group of nursing students poses different learning style and approximately half of them having predominantly a single style preference. There was a significant improvement in the students' performance after the intervention (F (1.69,506.92) = 237.22, P < .001). Discussion: Students' awareness of their strengths such as learning style preferences and how to utilize their strengths may improve their academic performance. Students should have awareness of their learning style and how to maximize their learning potential in the very early days of enrollment in the academic institution.